Tinjauan Kriminologis Mengenai Cyberbullying di Kota Makassar - Noviana, Nola (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This thesis, entitled Criminological Review of Cyberbullying in Makassar, is motivated because the author has seen many reports in the mass media about cyberbullying outside Makassar City, therefore the writer wants to examine cyberbullying cases in Makassar City. The problems discussed in this study are what are the factors that cause cyberbullying in Makassar City, how the impact of cyberbullying in Makassar City, as well as legal efforts made by law enforcement officials in tackling cyberbullying crimes in Makassar City. This study aims to determine and analyze the factors that cause cyberbullying in Makassar City, how the impact of cyberbullying in Makassar City, and what legal efforts are carried out by law enforcement officials in tackling cyberbullying crimes in Makassar City. This research was conducted at the Makassar City Police Department. The research method that I use is empirical juridical with data collection techniques in the form of literature studies and field studies by conducting interviews. The data obtained by the author are discussed qualitatively, and presented descriptively. Based on the results of research that the author can, it can be concluded that the factors causing cyberbullying in Makassar City are (1) factors of perpetrators of cyberbullying, (2) factors of victims of cyberbullying, (3) factors due to the absence of ethical social media, and (4) factors due to lack of public knowledge about cyberbullying, the impact of cyberbullying in Makassar City includes (1) the impact of cyberbullying victims, (2) the impact of the perpetrators of cyberbullying and (3) the impact on the community, mitigation efforts undertaken by law enforcement agencies regarding cyberbullying in Makassar City are ( 1) repressive measures and (2) preventive efforts. What we want to achieve from this research is to produce scientific papers in the form of theses, and research journals, which can be used as reference material for other writers in the future.